2023
DOI: 10.3390/civileng4030045
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Descriptive Analysis of Portuguese Public Procurement Data from 2015 to 2022

Abstract: During the tender phase of public construction projects in Portugal, documents that describe the project are mandatorily submitted to open data repositories. However, in their current state, most of these repositories do not allow for benchmarking analysis due to a lack of data treatment and cohesion. This paper seeks to diagnose the main trends during the public construction project’s tender phase by performing a descriptive statistical analysis on the Portuguese Public Procurement Database (PPPData), a datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a previous study, a descriptive statistical analysis was conducted on PPPData (Luís Jacques de Sousa et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, a descriptive statistical analysis was conducted on PPPData (Luís Jacques de Sousa et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…An initial descriptive statistical analysis performed in Luís Jacques de Sousa et al. (2023), on the dataset showed that the dataset is highly unbalanced regarding the output feature (the “Project Performance” class).…”
Section: Methodsmentioning
confidence: 99%